Groundswell : winning in a world transformed by social technologies - Li, Charlene, 1966-; Bernoff, Josh, ....- (Boston (Mass.) : Harvard Business Press, 2008)
Corporate executives are struggling with a new trend: people using online social technologies (blogs, social networking sites, YouTube, podcasts) to discuss products and companies, write their own news, and find their own deals. This groundswell is global, it's unstoppable, it affects every industry - and it's utterly foreign to the powerful companies running things now. When consumers you've never met are rating your company's products in public forums with which you have no experience or influence, your company is vulnerable. In Groundswell, Charlene Li and Josh Bernoff of Forrester, Inc. explain how to turn this threat into an opportunity. Using tools and data straight from Forrester, you'll learn how to: Evaluate new social technologies as they emerge Determine how different groups of consumers are participating in social technology arenas Apply a four-step process for formulating your future strategy Build social technologies into your business - including monitoring your brand value, talking with the groundswell through marketing and PR campaigns, and energizing your best customers to recruit their peers Timely and insightful, this book is required reading for executives seeking to protect and strengthen their company's public image.
Understanding the groundswell -- Why the groundswell--and why now? -- Jujitsu and the technologies of the groundswell -- The social technographics profile -- Tapping the groundswell -- Strategies for tapping the groundswell -- Listening to the groundswell -- Talking with the groundswell -- Energizing the groundswell -- Helping the groundswell to support itself -- Embracing the groundswell -- The groundswell transforms -- How connecting with the groundswell transforms your company -- The groundswell inside your company -- The future of the groundswell.
Includes bibliographical references (p. 247-263) and indexes.
Keywords: Information society -- Economic aspects; Marketing; Online social networks -- Economic aspects